Survey on production, human resources profile and training needs in the Chorotega region - Arias Ramírez, Rafael (2012)
This document is the report on the Survey of Production, Human Resource Profiles and Workforce Training Needs in the Chorotega Region. This survey forms part of the research project ‘Territorial Competitiveness and the Labour Market in the Chorotega Region’, carried out by the Institute for Economic Research at the University of Costa Rica (IICE). This survey is important for determining the quantitative and qualitative labour needs in the region and for informing public and private decision-makers regarding the policies and programmes that need to be implemented to improve human resource conditions in the region.